Answer:
![\sum_(n = 1)^(7) -2 -2n](https://img.qammunity.org/2022/formulas/mathematics/college/67ic0ms0fq3yi9qil7lcygsam77sbnvv64.png)
Explanation:
Arithmetic sequence:
In an arithmetic sequence, the difference of consecutive terms is always the same, called common difference.
The nth term of a sequence is given by:
![a_(n) = a_1 + (n-1)d](https://img.qammunity.org/2022/formulas/mathematics/college/tzsjygrwqllh1mydo993nih7cdlfg7bziq.png)
In which
is the first term and d is the common difference.
Sigma notation to represent the sum of the first seven terms
Sum going from the index starting at 1 and finishing at 7, that is:
![\sum_(n = 1)^(7) f(n)](https://img.qammunity.org/2022/formulas/mathematics/college/ygngcw52d2zgnldq1593xeoy79kpm6wwl6.png)
Now we have to fund the function, which is given by an arithmetic sequence.
−4, −6, −8,
First term -4, common difference - 6 - (-4) = -6 + 4 = -2, so
![a_1 = -4, d = -2](https://img.qammunity.org/2022/formulas/mathematics/college/k56q76b59yf73pe3ug2iv37m2p1dvxy1v5.png)
Then
![f(n) = a_(n) = a_1 + (n-1)d](https://img.qammunity.org/2022/formulas/mathematics/college/1jqzdj25f6239620fxjp3mhmbxzwzocjud.png)
![f(n) = -4 + (n-1)(-2)](https://img.qammunity.org/2022/formulas/mathematics/college/l9hvjne7sba784n0vhbmccspyxtle2ctsy.png)
![f(n) = -4 - 2n + 2 = -2 - 2n](https://img.qammunity.org/2022/formulas/mathematics/college/7ux0itmrhm784h0e503zyi8zotwv4ulish.png)
Sigma notation:
Replacing f(n)
![\sum_(n = 1)^(7) -2 -2n](https://img.qammunity.org/2022/formulas/mathematics/college/67ic0ms0fq3yi9qil7lcygsam77sbnvv64.png)